100 jaar schildersafdeling Glorieux Oostakker 1898-1998. - Popelier, Bert; Van Haesebrouck, Marc; Vermeulen, Luk (Oostakker : Technisch Insititut, 1998)
De Rycke, Perboyre ; van Meirhaeghe, Etienne ; Pieters, Piet ; Van Damme, Elie ; Schatteman, Henri ; Sinove, André ; Laheyne, Patrick ; Van Haesebrouck, Marc ; Nuyttens, André ; Verhaeghe, Roger ; Schatteman, Hendrik ; Van Puyenbroeck, Koenraad ; Vanlerberghe, Francisca ; Sergooris, Frederick
Nederlands
boek